Keefektifan Penggunaan Media Kartu Huruf terhadap Kemampuan Membaca Permulaan Siswa pada Mata Pelajaran Bahasa Indonesia Kelas I SD Negeri Widoro Tahun Ajaran 2022/2023 - Purbasari, Dyah Ayu; Palupi, Yulia (Pubmedia Jurnal Penelitian Tindakan Kelas Indonesia, 2023)
This study aims to determine the effectiveness of the use of letter cards on the ability to read beginning in the Indonesian language class I students at SD Negeri Widoro. This study used a quantitative research type and an experimental method with a pre-experimental design with the One Group Pretest-Posttest Design. This research does not use a comparison class but has used a pre-test so that the influence or effect of using letter card media can be known with certainty. Data collection techniques were carried out through observation and tests. Data were analyzed using a quantitative approach. The independent variable in this study is the letter card media. As well as the dependent variable is the ability to read at the beginning of class I SD Negeri Widoro, totaling 21 students. The sampling technique is saturated sampling. The results showed that in giving the posttest learning outcomes test which was analyzed using the t-test with the proportion = 7.80 > = 2.08 meaning that there is a difference in the use of letter card media on students' initial reading ability in Indonesian language class 1 SDN Widoro.